ANALISIS ASUHAN KEPERAWATAN PADA NY. A DAN NY. SJ DENGAN PENERAPAN TERAPI RELAKSASI NAFAS DALAM TERHADAP PENURUNAN TEKANAN DARAH - Wahidah, Alfiatun; Sari, Siska Mayang (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p06, 2023)
Elderly is someone who has reached the age of 60 years and over which is identified with a period of helplessness and decline. Hypertension is the most common disease suffered by the community, especially in the elderly, because this disease cannot be cured, serious treatment is needed. In addition to pharmacological therapy, non-pharmacological therapy also needs to be carried out in this case modifying lifestyle, reducing sodium intake, reducing stress and avoiding smoking. Non-pharmacological therapy also consists of complementary therapies such as acupuncture, relaxation techniques (deep breathing exercises). The method in scientific work is the analysis of nursing care at PSTW Khusnul Khotimah. Subjects consisted of 2 participants with hypertension problems and the intervention given was deep breathing relaxation therapy. The results of the implementation of deep breathing relaxation therapy which was done once a day for 3 days proved that there was a decrease in blood pressure, with an average decrease in blood pressure in Grandma A aged 67 years, namely systolic blood pressure of 8 mmHg and 8 mmHg diastolic, and in Grandma SJ is 80 years old, systolic blood pressure is 8 mmHg and diastolic is 5 mmHg. The author recommends the nurse as the person in charge of the homestead to continue the implementation of deep breath relaxation therapy once a day with a duration of 15 minutes.